2014
DOI: 10.1161/circresaha.116.304475
|View full text |Cite
|
Sign up to set email alerts
|

GRK5-Mediated Exacerbation of Pathological Cardiac Hypertrophy Involves Facilitation of Nuclear NFAT Activity

Abstract: Rationale G protein-coupled receptor (GPCR) kinases (GRKs) acting in the cardiomyocyte regulate important signaling events that control cardiac function. Both GRK2 and GRK5, the predominant GRKs expressed in the heart, have been shown to be up-regulated in failing human myocardium. While the canonical role of GRKs is to desensitize GPCRs via phosphorylation, it has been demonstrated that GRK5, unlike GRK2, can reside in the nucleus of myocytes and exert GPCR-independent effects that promote maladaptive cardiac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
101
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(109 citation statements)
references
References 44 publications
8
101
0
Order By: Relevance
“…To measure global cardiac function, echocardiography was performed with the VisualSonics VeVo 2100 imaging system in anesthetized animals (1.5% [vol/vol] isoflurane). The internal diameter of the left ventricle was measured in the short-axis view from M-mode recordings in end diastole and end systole as described previously (27).…”
Section: Methodsmentioning
confidence: 99%
“…To measure global cardiac function, echocardiography was performed with the VisualSonics VeVo 2100 imaging system in anesthetized animals (1.5% [vol/vol] isoflurane). The internal diameter of the left ventricle was measured in the short-axis view from M-mode recordings in end diastole and end systole as described previously (27).…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, additional reports argue that GRK5 can oppose NF-κB activity through mediating IκBα nuclear accumulation [84]. Furthermore, GRK5 augments nuclear factor of activated T cells (NFAT) transcriptional activity in an apparent kinase independent manner, potentially by some molecular scaffold activity [85]. …”
Section: Grk and Arrestin-mediated Signalingmentioning
confidence: 99%
“…However, recently we have shown a second novel action of GRK5 in the nucleus of myocytes. It was found that GRK5 interacts with the NFAT-pathway in the nucleus during pathological hypertrophy [55]. First, utilizing cardiac-specific NFAT luciferase reporter mice it was shown that GRK5 overexpression leads to an increase in NFAT activity while GRK5 KO mice exhibited less NFAT transcriptional activity [55].…”
Section: Non-canonical Novel Mechanisms Of Grk5-mediated Cardiac Pathmentioning
confidence: 99%
“…It was found that GRK5 interacts with the NFAT-pathway in the nucleus during pathological hypertrophy [55]. First, utilizing cardiac-specific NFAT luciferase reporter mice it was shown that GRK5 overexpression leads to an increase in NFAT activity while GRK5 KO mice exhibited less NFAT transcriptional activity [55]. Interestingly, double transgenic mice with cardiac-specific GRK5 over-expression and deletion of NFATc3 were protected from the early progression to HF observed with increased cardiac GRK5 levels following TAC[55].…”
Section: Non-canonical Novel Mechanisms Of Grk5-mediated Cardiac Pathmentioning
confidence: 99%